Criminal Liability for Violation of the Quarantine Regime in the Conditions of the COVID-19 Pandemic - Lemeshko, Oleksandr M.; Haltsova, Viktoriia V.; Brazhnyk, Andrii A. (International Journal of Criminology and Sociology, 2022)
Infectio us diseases is the subject of increased attention, which causes concern in society throughout the world. In this context, and in order to implement preventive measures, democratisation and protection of human rights are increasingly combined with measures of state coercion. The new challenge today is the COVID-19 pandemic, recognised by the World Health Organisation. Today is pandemic has forced a qualitative rethink of approaches to responding to the health challenges of both individuals and nations. States have gradually begun to use a variety of health measures, including policy and legal instruments, to control the spread and effects of COVID-19. Some states have resorted to criminal law to apply it to health care to prevent infection with COVID-19. A comparative analysis of the features of criminal liability for violating the quarantine regime in the European Union and Ukraine showed the variability of the structures of crimes, however, the unity of difficulties in qualifying socially dangerous acts and, as a result, the impossibility of effective prosecution. It was stated that there was an urgent need for States to recognise that the new coronavirus was a serious health emergency, but that the criminalisation related to COVID-19 was a worrying trend towards prolonging human rights restrictions. Experts are increasingly questioning, in particular, the feasibility and effectiveness of existing criminal law measures on health care and their fragmentary compliance with internationally declared human rights standards, which in the long run will be the basis for the abolition of new criminalised components of crimes.